Nanoliposomal Encapsulation Enhances In Vivo Anti-Tumor Activity of Niclosamide against Melanoma - Hatamipour, Mahdi; Jaafari, Mahmoud R.; Momtazi-Borojeni, Amir A.; Ramezani, Mahin; Sahebkar, Amirhossein (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Niclosamide is an FDA-approved and old anti-helminthic drug used to treat parasitic infections. Recent studies have shown that niclosamide has broad anti-tumor effects relevant to the treatment of cancer. However, this drug has a low aqueous solubility hindering its systemic use. Herein, we report the preparation and characterization of niclosamide nanoliposomes and their in vivo anti-tumor effects. Methods: Nanoliposomes were prepared using thin-film method and the drug was encapsulated with a remote loading method. The nanoliposomes were investigated by the observation of morphology, analysis of particle size and zeta potential. Additionally, qualitative and quantitative analyses were performed using HPLC. We assessed the in vitro cytotoxicity of the nanoliposomal niclosamide on B16F10 melanoma cells. Inhibition of tumor growth was investigated in C57BL/6 mice bearing B16F0 melanoma cancer. Results: Analytical results indicated that the nanoliposomal system is a homogeneous and stable colloidal dispersion of niclosamide particles. Atomic force microscopy images and particle size analysis revealed that all niclosamide particles had a spherical shape with a diameter of approximately 108nm. According to in vitro and in vivo studies, nanoliposomal niclosamide exhibited a better anti-tumor activity against B16F10 melanoma tumor compared with free niclosamide. Conclusion: Nanoliposomal encapsulation enhanced the aqueous solubility of niclosamide and improved its anti-tumor properties.
Keywords: cancer